Snow White and The Seven Dwarfs (The Original Magical Story, 2017)
When Ariel saves the life of a handsome prince called Eric, she dreams of living on land with the other humans. When the evil sea witch, Ursula, offers to help, Ariel risks everything for the chance to be with her prince. Will Ariel kiss the prince and live happily ever after, or will Ursula foil her plans? Enjoy a classic Disney experience with this magical storybook, Disney Princess The Little Mermaid The Original Magical Story.